STRATEGI MANAJEMEN MUTU DI SMK KANSAI PEKANBARU - Indra Wahyuni; Isjoni Isjoni; Zulfan Saam (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
This research aims to determine the quality management strategy at SMKKansai Pekanbaru. This research is a qualitative research. The core informant in this researchis the head of SMK Kansai Pekanbaru. As a control informant in this study are deputy principalof curriculum, vice principal of student field, vice principal of infrastructure, vice principal ofpublic relations, teacher, school committee and student. Data collection techniques are donethrough observation, interview and documentation study. Researchers also conductedtriangulation to compare observational data with data obtained from interviews anddocumentation. Then data obtained analyzed by using qualitative data analysis of interactivemodel consisting of data reduction, data presentation and conclusion. The result of the researchshows that: (1) The quality management strategy that is planned, compiled and implementedSMK Kansai Pekanbaru in order to improve the quality of education is referring to the TotalQuality Management (TQM) model, (2) The implementation process the principal superviseseach month and performs Evaluation on an ongoing basis to see how much the level ofachievement of the quality management strategy has been planned, (3) Factors supporting theimplementation process of quality management strategy at SMK Kansai Pekanbaru is theeducator who qualified S1 and S2 students according to the qualifications of the field he taught,(4) The process of implementation of quality management strategy at SMK Kansai Pekanbaruthere are also inhibiting factors, there are still some teachers who do not want to cooperate inthe case of improving the quality of school (5) To overcome the principal obstacle factors canovercome by giving rewards to teachers who discipline and carry out their main duties well inorder to improve the quality of school.